Liquid-Crystal Aromatic Polyesters Containing Azo and Sulfone Units - Yan Qiu, Ming; Sheng Niu, Yong; Zhu Yu, You; Hua Guo, Yu (Asian Journal of Chemistry, 2014)
Two novel aromatic polyesters containing azo and sulfone units were synthesized by poly-condensation of 4,4'-azobenzene-dicarbonyl chloride with dihydroxydiphenyl sulfones at low temperature. The synthesized polymers exhibited good solubility, inherent viscosity (reaches 1.05 dL g-1), high glass transition temperature (above 200 °C) and thermal stability (£ 5 % weight loss at 348 °C), which were characterized by Fourier transform infrared spectroscopy. The liquid crystalline and photoisomerization properties were observed by polarizing optical microscope and an ultraviolet-visible spectrophotometer.